Offspring Education, Mental Health Status and Quality of Life among Parents of High School Students in the Northeast of Thailand - Khamharnpol, T.; Banchonhattakit, P.; Laohasiriwong, W. (Kathmandu University Medical Journal, 2021)
Background Providing children best education could be burden on parents which might impaired their mental health and quality of life (QOL). Objective To assess children education, mental health status and their influence on QOL of parents of high school students in the Northeast of Thailand. Method This cross-sectional study was conducted among 1,098 parents of high school students. The study population were selected by using multistage random sampling from 20 high schools in 10 provinces of the Northeast of Thailand to response to a structured questionnaire interview. Multilevel logistic regression was performed to identify the influence of mental health status and offspring education on QOL of parents of high school students. Result Among the total of 1,098 respondents, 28.78% had poor quality of life. Factors that were associated with poor QOL of the parents were had moderate to severe depressive symptoms (adj.OR=5.72; 95% CI:4.01-8.16), had moderate to high levels of stress (adj.OR=2.32; 95% CI:1.64 - 3.29), not expected the child to study bachelor degree (adj.OR=2.59; 95% CI:1.74 -3.84), perceived children’s academic performance as not to minimal importance (adj.OR=2.20; 95% CI: 1.54 - 3.14), had 2 or more children currently studying (adj.OR= 1.62; 95% CI:1.00 - 2.64), and had low to high concerns on their children low examination scores (adj.OR=1.51; 95% CI: 1.06 - 2.15). Conclusion Depression, stress, children education as well as physical health and work-related problems had influence on QOL.